Inhibitory effect of oolonghomobisflavan B on osteoclastogenesis by suppressing p38 MAPK activation. Issue 18 (15th September 2020) - Lim, Soomin; Kim, Tae Hoon; Ihn, Hye Jung; Lim, Jiwon; Kim, Gi-Young; Choi, Yung Hyun; Bae, Jong-Sup; Jung, Jae-Chang; Shin, Hong-In; Kim, Jung-Eun; Park, Eui Kyun
Graphical abstract: Abstract: Suppression of differentiation and/or function of osteoclasts is considered an effective therapeutic strategy for osteolytic bone diseases such as periodontitis and osteoporosis. Evidence regarding the health benefits of oolong tea consumption is accumulating, and tea polyphenols have various pharmacological properties such as anti-cancer and anti-diabetes effects. In this study, we investigated the effect of oolonghomobisflavan B (OFB), a polyphenolic compound in oolong tea, on osteoclast differentiation. OFB suppressed receptor activator of nuclear factor-κB (RANKL)-induced formation of tartate-resistant acid phosphatase-positive multinuclear cells without cytotoxicity. OFB also significantly attenuated p38 phosphorylation, which is essential for RANKL-induced osteoclastogenesis, and inhibited the expressions of nuclear factor of activated T cells, cytoplasmic 1 (NFATc1) and osteoclast-specific target genes, including dendritic cell-specific transmembrane protein and cathepsin K. Our findings suggest that OFB exhibits an anti-osteoclastogenic activity by inhibiting RANKL-mediated p38 activation, which is useful for the prevention and treatment of osteolytic bone diseases.